Analisis efektivitas hukum di Indonesia terhadap pelanggaran hak cipta di Tiktok - Jannah, Faridatul (Maliki Interdisciplinary Journal, 2023)
To ensure the effective protection of copyright in TikTok, an analysis of the effectiveness of existing laws is required. An analysis of the effectiveness of the law in dealing with copyright-infringing content on TikTok needs to be carried out to evaluate the extent to which existing laws can protect copyright and deal with infringements that occur on this platform. The research methodology used in this study is based on normative juridical principles and involves the use of statutory approaches, conceptual approaches, and related principles and theories. The results of the study are that law enforcement on copyright regulated in the policies and provisions on the TikTok Platform has not been effective in providing protection to rights owners in terms of the implementation of the regulations and has not been effective due to obstacles from juridical factors that affect the effectiveness of law enforcement itself. To improve copyright protection in TikTok, it is very important to take more efficient measures such as improving the implementation of policies and regulations, encouraging greater collaboration between TikTok and copyright owners, and increasing user awareness about the importance of respecting the copyrights of others.